Annual Plant Reviews Online 2018
DOI: 10.1002/9781119312994.apr0627
|View full text |Cite
|
Sign up to set email alerts
|

Advances of Metabolite Profiling of Plants in Challenging Environments

Abstract: Plant metabolism is profoundly involved in physiological regulation and defence responses when the environment is adverse and plant growth and development is negatively affected. Metabolomics techniques allow the characterisation of physiological and biochemical responses to different types of environmental stresses in plants, including drought, salinity, and nutrient deficiencies. Metabolomics analyses of plant systems have been mostly carried out on bulked tissues (i.e. whole roots, leaves, or shoots) which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 207 publications
0
4
0
Order By: Relevance
“…44 The ability to resolve small histological foci using MALDI has created the need to advance these complementary molecular identification technologies to achieve similar spatial fidelity. 8,[47][48][49] The deposition of small volume droplets (<500 pL) of liquid (matrix or trypsin) is used routinely to profile discrete regions of tissue by MALDI MS. 9,50 This type of droplet-based deposition has been demonstrated to enable MS analysis of these tissue areas. For trypsin droplet deposition experiments, MALDI is typically used for analysis but LESA has also been demonstrated to be effective for extracting peptides from areas digested using LESAbased approaches.…”
Section: Graphical Abstractmentioning
confidence: 99%
“…44 The ability to resolve small histological foci using MALDI has created the need to advance these complementary molecular identification technologies to achieve similar spatial fidelity. 8,[47][48][49] The deposition of small volume droplets (<500 pL) of liquid (matrix or trypsin) is used routinely to profile discrete regions of tissue by MALDI MS. 9,50 This type of droplet-based deposition has been demonstrated to enable MS analysis of these tissue areas. For trypsin droplet deposition experiments, MALDI is typically used for analysis but LESA has also been demonstrated to be effective for extracting peptides from areas digested using LESAbased approaches.…”
Section: Graphical Abstractmentioning
confidence: 99%
“…The coordinated activation of primary and secondary metabolic pathways for antioxidants or N-and S-containing compounds under salt stress enable plants to (i) balance intracellular ROS level and redox status, (ii) activate the osmotic response network, and (iii) modulate the ROS-and/or osmotic-dependent signaling pathways (Bose et al 2014;Hossain and Dietz 2016;Sengupta et al 2016;Noctor et al 2018;Sarabia et al 2018;Surówka et al 2019;Wang et al 2019).…”
Section: The Role Of Primary and Secondary Metabolites In Response Tomentioning
confidence: 99%
“…It is therefore interesting to further study the lipid profiles of the roots of the two wheat varieties, especially on the different development root zones. Sarabia et al [ 44 , 45 ] and Ho et al [ 46 ] have recently reported comprehensive comparative spatial lipidomics analyses on different developmental root zones of barley subjected to salt stress and revealed cellular lipid remodeling in different developmental zones of barley roots in response to salinity. These results demonstrate the differential impact of salinity on different developmental root zones in each studied cultivar, as well as between different barley cultivars with differing levels of salinity tolerance.…”
Section: Introductionmentioning
confidence: 99%